Analysis Of Soccer Shooting Skills In Fifth Grade Students Of Pagerwojo O4 Elementery School Kesamben District - Yuda Yuana; Wiwik Kusmawati (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aims to analyze soccer shooting skills in fifth grade students of Pagerwojo 4 Elementary School, Kesamben District. The method used in this study is a quantitative descriptive method in which the researcher conducted a survey with a shooting skills test technique that refers to the assessment instrument in the Learning Implementation Plan that refers to the minimum learning completion that has been developed. The research sample of soccer shooting skills in fifth grade students of Pagerwojo 4 Elementary School, Kesamben District amounted to 31 children consisting of 17 girls and 14 boys. Based on the results of the study, it can be analyzed that soccer shooting skills in fifth grade students of Pagerwojo 4 Elementary School, Kesamben District are in the category of very poor at 0%, less at 22.6% (7 people), sufficient at 58.0% (18 people), good at 16.1% (5 people) and very good at 3.20% (1 person). From the average value of the soccer shooting skills of fifth grade students of Pagerwojo 4 Elementary School, Kesamben District, which is 50.8, this value is certainly far below the Minimum Competency (KKM) or has not been completed in learning outcomes with a value description of